HELIUM ACCUMULATION IN GROUNDWATER. II: A MODEL FOR THE ACCUMULATION OF THE CRUSTAL 4HE DEGASSING FLUX - Torgersen T.; Ivey G.N. (My University, 1985)
A model of 4 He accumulation in a confined aquifer is presented which includes in situ production and a crustal degassing flux of 4 He into the bottom of a confined aquifer. The model is consistent with the measurements of 4 He concentration in the Great Artesian Basin, Australia ( and , 1985) and also with the measurements of 4 He concentration in the Auob Sandstone of Namibia ( , 1981). The measured value of the crustal degassing flux of 4 He from these two areas is comparable with the 4 He degassing flux calculated from the atmospheric budget of 4 He ( et al. , 1963; and , 1983). A literature review suggests that a crustal degassing 4 He source may account for the 4 He accumulation in many other groundwater systems. It is concluded from the literature review, the detailed modelling of 4 He accumulation in GAB and the Auob Sandstone, and the atmospheric budget that crustal degassing of 4 He may be a common and widespread phenomena.